Pengaruh Pemberian NPK, IBA, dan GA3 (Giberelin Acid) Terhadap Pertumbuhan Vegetatif Tanaman Wortel (Daucus Carota Linnaeus.) pada Sistem Aeroponik - Nur Arsyika Yulia Putri; Rahmadina (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This research aims to determine the effect of NPK fertilizer, IBA, and GA3 on the vegetative growth of carrot plants (Daucus carota L.) in an aeroponic system. The study also employed a completely randomized design (CRD) with four treatments, namely control (P0), NPK 50 ml/L (P1), IBA 100 ml/L (P2), and GA3 25 ml/L (P3), each replicated three times. The observed parameters included plant height, stem diameter, number of leaves, root length, root surface area, and root volume. The results of the study showed that the application of NPK fertilizer had the most significant effect on vegetative growth, particularly in plant height, number of leaves, and root development, with an average increase of up to 50% compared to the treatments from the hormones. IBA hormone also plays a role in root formation and plant growth, while GA3 hormone increases plant height although with less influence compared to NPK and IBA. Thus, the aeroponics system combined with liquid NPK fertilizer has proven effective in supporting the vegetative growth of carrots.